Peran Humas dalam Organisasi Sosial - putri, Alika Rema; Marpaung, Charoline Renta Anggriani; Setiyadi, Bradley (Universitas Batanghari Jambi, 2024)
Public relations plays an important role in an organization. The engineering and management roles are the two primary responsibilities frequently identified in studies of public relations operations. Technician work covers all aspects of the art of public relations, including writing, editing, photographing, producing communications, organizing events, and corresponding by telephone with the media. media The methodology of this research is a type of literature study or literature review research. One way to conduct literature research is to collect references from several previous studies, which are then combined to produce findings. In modern practice, public relations cannot only be viewed as an institutional effort. It is everyone's responsibility to use public relations or public relations strategies to build effective interpersonal communication. different. This understanding of organizational management needs to be supported by advocacy for the establishment of a public relations division that can be relied on to manage organizational communication problems. Public relations plays an important role in an organization. The function of public relations is management in creating, maintaining and improving positive, harmonious and beneficial relationships between organizations and the general public. These relationships have the power to determine the success or failure of an organization. This is in line with the positive role played by public relations. As a result, the existence of public relations can influence the success or failure of an organization.